Находки личинок нематод надсемейства Acuarioidea (Spirurata) у рыб в Черном море - Пронькина, Н.В.; Белофастова, И.П.; Мачкевский, В.К. (Вестник зоологии, 2009)
Представлены новые находки личинок нематод надсемейства Acuarioidea у рыб Черного моря, которые являются паратеническими хозяевами этих нематод. Paracuaria adunca (Creplin, 1846) и Cosmocephalus obvelatus (Creplin, 1825) впервые зарегистрированы у Lipophrys pavo и Parablennius sanguinolentus (Bleniidae) и Neogobius ratan (Gobiidae). C. obvelatus впервые обнаружен у Liza saliens (Mugilidae), Pomatoschistus minutus elongates (Gobiidae) и Atherina boyeri pontica (Atherinidae). Приведены промеры и рисунки обнаруженных личинок. Обсуждены особенности реализации жизненных циклов этих нематод с использованием рыб, обитающих в прибрежных биоценозах черноморского мелководья. New finds of nematoda larvae of the superfamily Acuarioidea in the Black Sea fish (paratenic hosts for these nematodes) are recorded. Paracuaria adunca (Creplin, 1846) and Cosmocephalus obvelatus (Creplin, 1825) are recorded from Lipophrys pavo and Parablennius sanguinolentus (Bleniidae) and Neogobius ratan (Gobiidae), whereas C. obvelatus is found in Liza saliens (Mugilidae), Pomatoschistus minutus elongates (Gobiidae) and Atherina boyeri pontica (Atherinidae) for the first time. Measurements and figures of found larvae are presented. Peculiarities of life cycle realization in these nematodes with use of fish, dwelling coastal biocenoses of the Black Sea shoal are discussed.